2019
DOI: 10.1111/ropr.12342
|View full text |Cite
|
Sign up to set email alerts
|

Polycentric Systems and Multiscale Climate Change Mitigation and Adaptation in the Built Environment

Abstract: Addressing climate change requires consideration of mitigation and adaptation opportunities at multiple spatial scales. This is particularly true in the built environment, defined here to include individual buildings, neighborhoods, and the spaces between. The current U.S. political environment portends fewer resources and coordinating services for mitigation and adaptation at the federal level, however, reinforcing the relevance and necessity of actions at subnational levels. In this study, we evaluate the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…Potentially fruitful points of departure for future analysis include a more in-depth investigation into the presence of CLEG systems in different contexts (see Andonova et al, 2009; Ba & Galik, 2019) as well as their interplay with state and civil society members. In addition, theorization of the interaction between corporate-led governance arrangements and environmental policy processes is needed to advance the knowledge on the positionality of CLEG solutions in environmental policy-making, in particular regarding the shifting roles of and venues for different stakeholders and the technical and ideological feasibility of different policy instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially fruitful points of departure for future analysis include a more in-depth investigation into the presence of CLEG systems in different contexts (see Andonova et al, 2009; Ba & Galik, 2019) as well as their interplay with state and civil society members. In addition, theorization of the interaction between corporate-led governance arrangements and environmental policy processes is needed to advance the knowledge on the positionality of CLEG solutions in environmental policy-making, in particular regarding the shifting roles of and venues for different stakeholders and the technical and ideological feasibility of different policy instruments.…”
Section: Discussionmentioning
confidence: 99%
“…These actions lay a possible foundation for a robust polycentric approach to climate change in the United States. For example, examining climate mitigation and adaptation policies in the US associated with the built environment, including residential and commercial buildings, Ba and Galik (2019) found that such policies met the criteria of a functional polycentric governance system established by Carlisle and Gruby (2019). Yet, even as progress happens across sub-governments with a weakly polycentric approach, more collaboration and coordination are likely needed to produce a robust and functional polycentric governance approach to climate change.…”
Section: Polycentricity and Climate Changementioning
confidence: 99%
“…Araos and others (2017) assert that multilevel governance can be better applied to low‐income regions with limited financial, human, and natural resource and higher reliance on central governments. Dovers and Hezri (2010), Thomas and others (2019), and Ba and Galik (2019) identify multilevel governance as a means of achieving adaptation, highlighting it is an effective way to reduce vulnerability and climate change mitigation and adaptation in the built environment.…”
Section: Multilevel Governance Vulnerability‐readiness Nexus and Anmentioning
confidence: 99%